Keunggulan Penerapan Design Thinking dalam Pembelajaran pada Tingkat Sekolah Menengah Atas - Anggi Septia Pramaista; Eka Maya Putri Anggraeni; Fahmi Dwi Septiani; Lussana Rossita Dewi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
21st-century learning demands the development of critical thinking, creativity, collaboration, and problem-solving skills in senior high school (SMA) students. Design thinking is considered relevant, because it emphasizes empathy-based problem solving, ideation, and iteration through the stages of empathize, define, ideate, prototype, and test. This study aims to analyze the advantages of implementing design thinking in senior high school learning through a systematic literature review. The study was conducted on 10 research articles published in the period 2019-2025, obtained from the Google Scholar database, ScienceDirect, and accredited national journals. Articles were selected based on the following inclusion criteria: 1) discussing the application of design thinking at the senior high school level; 2) containing empirical results or learning-based community service; and 3) relevant to the development of 21st-century competencies. Data analysis used content analysis techniques with thematic synthesis. The results of the synthesis showed a dominant pattern, that design thinking consistently improves critical thinking and problem-solving skills, especially through contextual problem exploration and prototype activities. This approach also tends to strengthen student creativity, motivation, and learning engagement through collaboration and open ideation, and encourages the integration of user-centered learning technologies. These findings confirm the contribution of design thinking as an effective approach in bridging learning theory and practice and supporting the strengthening of 21st-century competencies and the Pancasila Student Profile at the high school level.